Violations of Politeness in the Dialogue of the Horror Comedy Film Sekawan Limo: A Pragmatic Study - Veronika Desantis Kire Wea; Widyatmike Gede Mulawarman (Transpublika Publisher, 2026)
The phenomenon of violations of the principles of politeness in language found in the dialogue of the horror comedy film Sekawan Limo. Theoretically, the principle of politeness functions to maintain harmonious social interactions. In the context of the film, violations of this principle are utilized as a communicative strategy to introduce elements of humor and strengthen characterization. This study aims to describe the forms of violations of politeness maxims, identify the types of maxims violated, and analyze the pragmatic function of these violations in character formation and storyline development. This study uses a descriptive qualitative approach with a pragmatic study based on Leech’s (1993) theory of politeness. The research data consists of dialogue utterances in the film Sekawan Limo, collected through listening and note-taking techniques. Data analysis was conducted by identifying speech acts containing violations, classifying them based on the six maxims of politeness, analyzing the context of the speech situation, and interpreting the pragmatic functions underlying them. The results showed that violations occurred in the maxims of politeness, namely the maxims of tact, generosity, praise, and sympathy. These violations were realized through the use of harsh remarks, mockery, sarcasm, and direct speech that belittled the interlocutor. Politeness violations in Sekawan Limo mainly arose in equal, intimate relationships and emotional situations. Functionally, they acted as pragmatic strategies to generate humor, highlight character traits, and drive conflict. These violations are not mere linguistic deviations but contextual, functional phenomena, whose use in media must consider ethical and social implications.